ONE STRAIN-MANY COMPOUNDS (OSMAC) METHOD FOR PRODUCTION OF PHENOLIC COMPOUNDS USING Camarops sp., AN ENDOPHYTIC FUNGUS FROM Alibertia macrophylla (Rubiaceae) - Gubiani, Juliana R. [UNESP]; Habeck, Thomas R. [UNESP]; Chapla, Vanessa M.; Silva, Geraldo H.; Bolzani, Vanderlan S. [UNESP]; Araujo, Angela R. [UNESP] (Soc Brasileira Quimica, 2016)
Seven phenolic derivatives including p-hydroxyphenyllactic acid (1), p-hydroxybenzoic acid (2), p-hydroxybenzaldehyde (3), phenyllactic acid (4), n-butyl-3,4-dihydroxybenzoate (5), n-hexyl-3,4-dihydroxybenzoate (6) and n-octyl-3,4-dihydroxybenzoate (7) were produced using Camarops sp. via the one strain-many compounds (OSMAC) approach. Their structures were determined using 2D NMR and ESI-MS spectra and were compared with works reported in the literature. This paper deals with the first report of these compounds in Camarops sp.
Keywords: endophytic fungus; Camarops sp.; phenolic compounds